Black banners of ISIS : the roots of the new caliphate - Wasserstein, David (New Haven : Yale University Press, 2017)
A medieval Islam historian's incisive portrait of ISIS, revealing the group's deep ideological and intellectual roots in the earliest days of Islam. With tremendous speed, the Islamic State has moved from the margins to the center of life in the Middle East. Despite recent setbacks, its ability to conquer and retain huge swaths of territory has demonstrated its skillful tactical maneuvering, ambition, and staying power. Yet we still know too little about ISIS, particularly about its deeper ideology. In this eye-opening book, David J. Wasserstein offers a penetrating analysis of the movement, looking closely at the thousand-year-old form of Islamic apocalyptic messianism the group draws upon today. He shows how ISIS is not only a military and political movement but also, and primarily, a religious one with a coherent worldview, a patent strategy, and a clear goal: the re-creation of a medieval caliphate. Connecting the group's day-to-day activities and the writings and sayings of its leaders with the medieval Islamic past, Wasserstein provides an insightful and unprecedented perspective on the origins and aspirations of the Islamic State.
Introduction : the Islamic State -- Caliphate -- Administration -- Revenue -- Religion -- Women, and children too -- Christians and Jews and ... -- Apocalypse now -- Conclusion.
Includes bibliographical references (pages 213-255) and index.
Keywords: IS (Organization) -- History; IS (Organization); 2000-2099; Terrorism -- Religious aspects -- Islam; Terrorists -- Iraq; Terrorists -- Syria; Terrorism -- Middle East; HISTORY / Middle East; RELIGION / Islam / History; RELIGION / Islam / Law; Terrorism; Terrorism -- Religious aspects -- Islam; Terrorists